Difficult choledocholithiasis – result of overdue surgical treatment of gallstone disease - S. G. Shapovalyants; T. B. Ardasenov; A. G. Pankov; S. A. Budzinsky; V. S. Veselova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze results of diagnostics and treatment of difficult forms of choledocholithiasis.Material and methods. Difficult forms of choledocholithiasis (large size, atypical improper shape and localization of stones, alteration of anatomy of pancreatobiliary area) were revealed in 275 patients. At admission obstructive jaundice was present in 202 (73,5%) of them, cholangitis – in 67 (24,4%), acute biliary pancreatitis – in 8 (2,9%). Surgical treatment was started with transpapillary operations.Results. In 12 (4,4%) patients transpapillary procedures appeared to be impossible, all of them have been operated by surgically. Endoscopic operations were carried out for remainder 263 patients (95,6%) that allowed to resolve obstructive jaundice, and only at 65,8% of patients – to sanify bile ducts completely. Complications of endoscopic treatment developed in 22 (8,4%) cases. The surgical choledocholititomy was executed in 57 patients, complications develop in 21 (36,8%). The mortality in group with difficult choledocholithiasis was 5,1%. At analysis of the causes of neglect of disease in difficult choledocholithiasis patients it was revealed, that the majority of them (217 – 78,9%) had a long history of gallstone disease (GSD). Various surgical interventions for biliary tracts were carried out to 27 patients. Part of patients (84) received conservative therapy for biliary colic and complications of GSD, abandoning of operative treatment resulted in, first, development of severe complication – choledocholithiasis, second, development of unfavorable anatomical conditions for its noninvasive resolution.Conclusion. Complex anatomical conditions in patients with choledocholithiasis basically develop as a result of overdue surgical treatment of gallstone disease. The main cause of delay in cholecystectomy is unjustified long-term and ineffective conservative treatment.